2014
DOI: 10.1038/srep04404
|View full text |Cite
|
Sign up to set email alerts
|

Boundary layer flow and heat transfer over a nonlinearly permeable stretching/shrinking sheet in a nanofluid

Abstract: The steady boundary layer flow and heat transfer of a nanofluid past a nonlinearly permeable stretching/shrinking sheet is numerically studied. The governing partial differential equations are reduced into a system of ordinary differential equations using a similarity transformation, which are then solved numerically using a shooting method. The local Nusselt number and the local Sherwood number and some samples of velocity, temperature and nanoparticle concentration profiles are graphically presented and disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(59 citation statements)
references
References 42 publications
1
55
0
Order By: Relevance
“…Important work on the boundary layer flow of a nanofluid over a stretching sheet has been reported by Khan and Pop [8], Rana and Bhargava [9] conducted similar research for a nonlinear stretching sheet, Mabood et al [10] reported MHD boundary layer flow and heat transfer of nanofluids over a nonlinear stretching sheet. Numerous researchers [11][12][13][14][15][16] reported related studies for linear/nonlinear stretching sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Important work on the boundary layer flow of a nanofluid over a stretching sheet has been reported by Khan and Pop [8], Rana and Bhargava [9] conducted similar research for a nonlinear stretching sheet, Mabood et al [10] reported MHD boundary layer flow and heat transfer of nanofluids over a nonlinear stretching sheet. Numerous researchers [11][12][13][14][15][16] reported related studies for linear/nonlinear stretching sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Rana and Bhargava [24] used finite element and finite difference methods for nonlinear stretching sheet problem. Zaimi et al [25] extended the work of Rana and Bhargava and they studied heat transfer and steady boundary layer flow of a nanofluid over a stretching/shrinking sheet. Effect of heat generation or absorption on nanofluid flow over a vertical plate was discussed by Ghalambaz and Noghrehabadi [26].…”
Section: Introductionmentioning
confidence: 95%
“…The non-linear coupled equations (11) and (12) along with boundary conditions (13) Rana and Bhargava (2012) and Zaimi et al (2014) figure 2, we can see that two different classes (types) of boundary layers. In the first class, the velocity of fluid inside the boundary layer decreases from the surface towards the edge of the layer ( 1   ) and in the second type the fluid velocity increases from the surface towards the edge ( 1   ).…”
Section: Numerical Solutionmentioning
confidence: 99%